Subgingival Host-Microbial Interactions in Hyperglycemic Individuals. (June 2020) - Kumar, P.S.; Monteiro, M.F.; Dabdoub, S.M.; Miranda, G.L.; Casati, M.Z.; Ribeiro, F.V.; Cirano, F.R.; Pimentel, S.P.; Casarin, R.C.V.
Type 2 diabetes mellitus (T2DM) is an established risk factor for periodontitis, yet its contribution to creating host-bacterial disequilibrium in the subgingival crevice is poorly understood. The present investigation aimed to quantify the impact of hyperglycemia on host-bacterial interactions in established periodontitis and to map shifts in these dynamics following mechanical nonsurgical therapy. Seventeen T2DM and 17 non-T2DM subjects with generalized severe chronic periodontitis were recruited along with 20 periodontally healthy individuals. Subjects with periodontitis were treated with scaling and root planing (SRP). Samples of subgingival biofilm and gingival crevicular fluid were collected at baseline and at 1-, 3-, and 6 mo postoperatively. Correlations were generated between 13.7 million 16S ribosomal DNA sequences and 8 immune mediators. Intermicrobial and host-microbial interactions were modeled using differential network analysis. Periodontal health was characterized by a sparse interbacterial and highly connected cytokine-bacterial network, while both normoglycemics and T2DM subjects with periodontitis demonstrated robust congeneric and intergeneric hubs but significantly fewer cytokine-bacterial connections. Following SRP, the cytokine-bacterial edges demonstrated a 2-fold increase 1 mo postoperatively and a 10-fold increase at 6 mo in normoglycemics. In hyperglycemics, there was a doubling at 1 mo but no further changes thereafter. These shifts accompanied an increasingly sparse interbacterial network. In normoglycemics, the nodes anchored by interleukin (IL)–4, IL-6, and IL-10 demonstrated greatest rewiring, while in hyperglycemics, IL-1β, IL-6, INF-γ, and IL-17 exhibited progressive rewiring. Thus, the present investigation points to a breakdown in host-bacterial mutualism in periodontitis, with interbacterial interactions rather than host-bacterial interactions primarily determining community assembly. Hyperglycemia further exacerbates this uncoupled mutualism. Our data also demonstrate that while nonsurgical therapy might not consistently alter microbial abundances or lower proinflammatory molecules, it "reboots" the interaction between the immunoinflammatory system and the newly colonizing microbiome, restoring a role for the immune system in determining bacterial colonization. However, this outcome is lower and delayed in hyperglycemics.